"Bullies tend to be obvious": autistic adults perceptions of friendship and the concept of 'mate crime'. Issue 7 (8th August 2020) - Forster, Samantha; Pearson, Amy
Abstract: Mate crime is a specific subset of hate crime in which the perpetrator is known to the victim. The aim of the current study was to examine perceptions of friendship and the concept of mate crime in autistic adults. Five adults were interviewed about their experiences of social interactions, friendships and mate crime. Interpretative Phenomenological Analysis revealed three superordinate themes: (1). Perceptions and 'learning the formula' (2). Socialising… 'It's more complicated than that', and (3). 'Taking Advantage of You'. Themes highlight the importance of further research into positive and negative aspects of social relationships in autistic adults, and the need to challenge attitudes around disability and provide support to those who may be socially vulnerable.